2019
DOI: 10.5551/jat.47654
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutritional and Inflammation Status on Long-Term Bleeding in Patients Undergoing Percutaneous Coronary Intervention with an Oral Anticoagulant

Abstract: Aim: Patients undergoing percutaneous coronary intervention (PCI) who require both oral anticoagulant (OAC) and antiplatelet therapy (APT) are exposed to a serious risk of bleeding. The aim of this study was to clarify the relationship among nutritional and inflammation status and long-term bleeding in patients requiring both OACs and APT after PCI. Methods: We performed PCI in 3,718 consecutive patients between April 2011 and March 2017, 302 of whom were treated with both OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…As an indicator of inflammation, hs-CRP has been thought to be closely related to the risk of death and ischemic events in patients with CHD ( 18 20 ). The results of this study showed that the higher hs-CRP was, the patient presented more HTPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an indicator of inflammation, hs-CRP has been thought to be closely related to the risk of death and ischemic events in patients with CHD ( 18 20 ). The results of this study showed that the higher hs-CRP was, the patient presented more HTPR.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory biomarkers have also become the therapeutic target for CHD in era of “poststatins,” as recent CANTOS ( 12 ) and LoDoCo2 ( 13 ) trails established that anti-inflammation improves the prognosis of CHD. Previous studies have shown that elevated leukocyte count ( 14 17 ) and hs-CRP ( 18 20 ) were associated with bleeding and thrombotic adverse events in PCI patients, however, the mechanism of the increased risk is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Yoshida et al found that low GNRI and hs-CRP were predictors of bleeding risk in patients requiring antiplatelet therapy after PCI. 27 Katsanos et al showed that clopidogrel monotherapy was associated with the most favorable harm-benefit profile without being associated with an increased risk of severe bleeding in PAD patients. 28 Furthermore, a recent study also reported that clopidogrel therapy extended beyond 12 months was associated with decreased risk of all-cause death or non-fatal MI in DM patients after second-generation drug-eluting stent implantation in PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in a retrospective study that included 3718 consecutive patients who underwent percutaneous coronary interventions, a low geriatric nutritional risk index and high-sensitivity C-reactive protein were correlated with a 5-fold increase in the incidence of Bleeding Academic Research Consortium class ≥3 bleeding. 35 However, these specific predictors were not evaluated in the current protocol because these data were published after the study was initiated. Moreover, the purpose of this study was to develop a simple and not particularly demanding bleeding score that could be rapidly utilized in preprocedural safety assessment.…”
Section: Discussionmentioning
confidence: 99%